Potential synthetic lethality for breast cancer: A selective sirtuin 2 inhibitor combined with a multiple kinase inhibitor sorafenib - Hua-Li Wang; Xue Ma; Xin-Yuan Guan; Chen Song; Guo-Bo Li; Ya-Mei Yu; Ling-Ling Yang (Elsevier, 2022)
Sorafenib is a clinically useful multiple kinase inhibitor for the treatment of kidney cancer, liver cancer and acute myelocytic leukemia, while it has shown weak efficacy in suppressing breast cancer. Since sirtuin2 (SIRT2) is an important epigenetic regulator and associated with several cancer types including breast cancer, development and evaluation of new SIRT2 inhibitors to probe their therapeutic potentials is currently desirable. A highly selective SIRT2 inhibitor named I was previously developed by us, which showed activity to inhibit non-small cell lung cancer cell lines in vitro. We herein report expanded screening of I and its structurally similar inactive compound II against other cancer cell lines, and found that I had a wide spectrum of anticancer activity while II had no such effects. The I-sorafenib combination treatment exerted obvious synergistic reduction on cell viability of MCF-7 cells. We observed that the combination treatment could suppress cell proliferation, survival and migration, arrest cell cycle at G0/G1 phase, and induce apoptosis in MCF-7 cells, when compared with the single treatment. In vivo studies revealed that the combination treatment showed stronger tumor growth inhibition (87%), comparing with I-(42.8%) or sorafenib-solely-treated groups (61.1%) in MCF-7 xenograft model. In conclusion, this work clearly revealed a potential synthetic lethality effect for I combined with sorafenib, and will probably offer a new strategy at least for breast cancer treatment.